2017
DOI: 10.1590/0102-33062016abb0255
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and fruit availability of the babassu palm ( Attalea speciosa Mart. ex Spreng) in human-dominated landscapes of the Northeast Region of Brazil

Abstract: We studied the population structure and fruit availability of the babassu palm, Attalea speciosa, in three humandominated landscapes located near a rural community in the region of Araripe, in the Northeast Region of Brazil, that were under intense fruit harvest. Fifty 10 x 10 m plots were randomly established in each of the three landscapes, and all individuals of A. speciosa within the plots were classifi ed as seedlings, juveniles or adults, with the height of all adult individuals being measured. An additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In addition to the characteristic crown shape, they also show distinctive ecological behaviour, such as Attalea speciosa, which has a prominent star-shaped crown and is common and distributed in all the Amazon forest. It is a pioneer species known for the invasion of pastures and can even be the cause of abandonment of the land [24,25]. Some palm species are also indicators of past occupation in the Amazon forest, as it has been demonstrated for the anthropogenic soils called 'terra preta' in the Amazon [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the characteristic crown shape, they also show distinctive ecological behaviour, such as Attalea speciosa, which has a prominent star-shaped crown and is common and distributed in all the Amazon forest. It is a pioneer species known for the invasion of pastures and can even be the cause of abandonment of the land [24,25]. Some palm species are also indicators of past occupation in the Amazon forest, as it has been demonstrated for the anthropogenic soils called 'terra preta' in the Amazon [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The eight-fold increment in S. coronata population density we documented is much higher than those reported for other palm species in disturbed habitats (e.g. Campos et al 2017, Martínez-Ramos et al 2016. Increments in arboreal palm density across disturbed forest habitats are commonly associated with an increase in light incidence (Souza & Martins 2003) and changes in the rates of seed predation and dispersal (Pimentel & Tabarelli 2004, Wright et al 2000.…”
Section: Discussionmentioning
confidence: 45%
“…In fact, S. coronata appears to be a stress-tolerant and aggressive colonizer, as are other lightdemanding palm species, e.g. Attalea humilis, A. oleifera, A. speciosa (Aguiar & Tabarelli 2010, Campos et al 2017, Henderson et al 1995, Lorenzi et al 2004, May et al 1985. Moreover, farmers frequently leave some palms when clearing forest for pasture or crops as they are useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a portion of the population wants to eliminate it, another part wants to maintain it because of its multiple uses, Araújo and Lopes (2012). Some plot-scale work has demonstrated higher densities of adult babassu in pastures than in the original forest, Anderson (1983); Campos et al (2017), while other work has shown the opposite, Barot et al (2005). A territory-wide study of the PA-Benfica smallholder farming community revealed this variability in the density of babassu cauliflower palms in primary forests as well as in pastures and secondary forests.…”
Section: Introductionmentioning
confidence: 99%